Glibenclamide-Induced Autophagy Inhibits Its Insulin Secretion-Improving Function in β Cells - Jiali Zhou; Xincong Kang; Yushuang Luo; Yuju Yuan; Yanyang Wu; Meijun Wang; Dongbo Liu (International Journal of Endocrinology)
Diabetes is a metabolic disease, partly due to hypoinsulinism, which affects ∼8% of the world’s adult population. Glibenclamide is known to promote insulin secretion by targeting β cells. Autophagy as a self-protective mechanism of cells has been widely studied and has particular physiological effects in different tissues or cells. However, the interaction between autophagy and glibenclamide is unclear. In this study, we investigated the role of autophagy in glibenclamide-induced insulin secretion in pancreatic β cells. Herein, we showed that glibenclamide promoted insulin release and further activated autophagy through the adenosine 5′-monophosphate (AMP) activated protein kinase (AMPK) pathway in MIN-6 cells. Inhibition of autophagy with autophagy inhibitor 3-methyladenine (3-MA) potentiated the secretory function of glibenclamide further. These results suggest that glibenclamide-induced autophagy plays an inhibitory role in promoting insulin secretion by activating the AMPK pathway instead of altering the mammalian target of rapamycin (mTOR).